2000
DOI: 10.1002/1521-3765(20001201)6:23<4400::aid-chem4400>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Physical Investigation of Donor–Donor and Acceptor–Acceptor End-Functionalized Monodisperse Poly(triacetylene) Oligomers

Abstract: Two series of monodisperse, terminally donor-donor [D-D, D=4-(dimethylamino)phenyl] and acceptor-acceptor [A-A, A=4-nitrophenyl] functionalized poly(triacetylene) (PTA) oligomers ranging from monomer to hexamer were synthesized by oxidative Hay oligomerization under end-capping conditions. The corresponding D-D and A-A end-substituted polymers with an average degree of polymerization (DP) of n approximately 18 and n approximately 12, respectively, were also prepared and served as reference points for the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…According to the different approaches of this issue, some studies have reported molecular chromophores or conjugated polymers exhibiting a large third-order nonlinear susceptibility in their transparency range, or a large nonlinear index satisfying the requirements imposed by the material's figures-of-merit [2] defined for photonic switching applications. Typically, this has been addressed in several push±pull molecules (stilbenes, [4a,b] azobenzenes, [4b±d] tetraethynylethenes, [4e] diphenylpolyenes, [4f] 3,3¢-bipyridines [4g] ) and conjugated polymers (para-toluene sulfonate, [5] polyphenylvinylenes [6] ) based on the classical dipolar electronic structure, but also, with further prospects, in non-dipolar chromophores or polymers exhibiting an apolar (tetraethynylethenes, [4e] 3,3¢-bipyridines, [4g] polytriacetylenes [7] ), quadrupolar (tetraethynylethenes [4e,8] ), or octupolar (thiophene-based triazines [9] ) molecular geometry.…”
Section: Introductionsupporting
confidence: 54%
“…According to the different approaches of this issue, some studies have reported molecular chromophores or conjugated polymers exhibiting a large third-order nonlinear susceptibility in their transparency range, or a large nonlinear index satisfying the requirements imposed by the material's figures-of-merit [2] defined for photonic switching applications. Typically, this has been addressed in several push±pull molecules (stilbenes, [4a,b] azobenzenes, [4b±d] tetraethynylethenes, [4e] diphenylpolyenes, [4f] 3,3¢-bipyridines [4g] ) and conjugated polymers (para-toluene sulfonate, [5] polyphenylvinylenes [6] ) based on the classical dipolar electronic structure, but also, with further prospects, in non-dipolar chromophores or polymers exhibiting an apolar (tetraethynylethenes, [4e] 3,3¢-bipyridines, [4g] polytriacetylenes [7] ), quadrupolar (tetraethynylethenes [4e,8] ), or octupolar (thiophene-based triazines [9] ) molecular geometry.…”
Section: Introductionsupporting
confidence: 54%
“…TEE dimer 13 is oxidized in two twoelectron steps at 0.37 and 0.54 V, centered on its four dimethylanilino groups. [37] The reduction at À 1.61 V is a reversible one-electron transfer occurring on the central carbon core; the same reduction potential was measured for TEE dimer 6 bearing two dimethylanilino groups. A similar redox behavior is expectedly found for 14 with four (H 25 C 12 ) 2 NC 6 H 4 groups.…”
Section: Resultsmentioning
confidence: 99%
“…The electron-donating dialkylanilino groups present in 13 and 14 make the first reduction more difficult by about 100 mV relative to the dimers 9 and 12. The push ± pull dimer 16 is reduced in two one-electron steps, centered on the two nitrophenyl groups, [37] which potentials (À 1.35 and À 1.28 V) are separated by 70 mV. Similarly, the oxidation of its two dialkylanilino groups occurs in two distinct one-electron oxidation steps at 0.45 and 0.56 V. In the extended chromophore 17, the four dialkylanilino groups are oxidized in two two-electron steps, similar to 13.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PTA mono-, di-, tri-, tetra-, penta-, and hexamers 41a-f and 42a-f ( Figure 18) provide useful information regarding the influence of donor-donor (D-D) and acceptor-acceptor (A-A) substitution in the end groups of PTAs based on the trans-1,2-diethynylethene repeat unit [45]. As reference points for the infinitely long polymers, compounds 41g and 42g (@18 and 12 DEE units) were studied.…”
Section: Donor-donor and Acceptor-acceptor End-functionalizationmentioning
confidence: 99%